Pengaruh Terpaan Iklan dan Terpaan Konten Celebrity Endorsement Terhadap Minat Menggunakan Jasa Go-Food (Melalui Brand Attitude) - Karunia Yusuf, Kevin; Pradekso, Tandiyo (Interaksi Online, 2021)
This research is based on Go-Food’s consumers behaviour and persuasive messages that are distributed through a digital campaign. The purposes of this study are evaluating the effect of advertising exposure and celebrity endorsement exposure on intention to purchase Go-Food services via brand attitude as a mediator. Cognitive response theory has been used to link the variables in this study. This study benefited from the use of quantitative research method. The population of this study including men and women living in Semarang, aged 18-34, who had received the exposure of advertising in Protokol #J3K campaign. Data analysis used to test the hypotheses was SEM-PLS, with the help of SmartPLS3 application. The result shows that there is a positive effect from advertising exposure, advertorial exposure, and celebrity endorsement exposure on brand attitude, most of them are significant. It has also been found an enormous effect from brand attitude on Intention to Purchase. This study also found that Brand Attitude does not fully mediate the effect from advertising exposure, advertorial exposure, and celebrity endorsement exposure on intention to purchase.